2020
DOI: 10.1002/btm2.10204
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐thin, high strength, antibiotic‐eluting sutures for prevention of ophthalmic infection

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Prevention and treatment of ocular infection in rats was assessed using a previously described model with minor adjustments. 56 S. aureus bacteria were propagated on nutrient agar plates followed by incubation at 37°C for 16 h. The bacterial colonies were collected and suspended in sterile PBS to obtain bacterial count of 1 × 10 8 CFU/ml. Rats received general anesthesia prior to applying a drop of 0.5% proparacaine hydrochloride ophthalmic solution to the cornea.…”
Section: Methodsmentioning
confidence: 99%
“…Prevention and treatment of ocular infection in rats was assessed using a previously described model with minor adjustments. 56 S. aureus bacteria were propagated on nutrient agar plates followed by incubation at 37°C for 16 h. The bacterial colonies were collected and suspended in sterile PBS to obtain bacterial count of 1 × 10 8 CFU/ml. Rats received general anesthesia prior to applying a drop of 0.5% proparacaine hydrochloride ophthalmic solution to the cornea.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2020 study, a drug-eluting suture was developed for ocular delivery of levofloxacin which indicated a 30-days drug release and efficacy against bacterial keratitis in rat eyes. 51 Mirzaeei et al designed nanofibrous matrices for ocular delivery of ofloxacin indicated the sustained release of drug through 96 h and improved pharmacokinetics compared to the drug solution. 52 An enhanced in vitro antibacterial activity was reported by levofloxacin ocular nanospheres in another study.…”
Section: In Vitro Release and Kineticsmentioning
confidence: 99%
“…The growing demand for versatile, biocompatible synthetic polymers in biomedical engineering and medical devices has galvanized research beyond the biocompatibility and tissue‐regenerative ability of FDA‐approved synthetic polymers such as polycaprolactone (PCL), poly(methyl methacrylate) (PMMA), poly(lactic‐co‐glycolic acid) (PLGA), and polyurethanes (PU) and toward the design of more tailorable polymeric materials with enhanced biological and mechanical properties 1–5 . PU‐based polymers have recently attracted substantial interest for use in various tissue‐regenerative processes, including muscle, cartilage, blood vessel and bone regeneration, because of their tunable properties, such as biodegradability, elasticity and resistance to flex fatigue 6–10 .…”
Section: Introductionmentioning
confidence: 99%